A ramp capability-aware scheduling strategy for integrated electricity-gas systems. (15th February 2022) - Zhang, Mingyang; Zhou, Ming; Wu, Zhaoyuan; Yang, Hongji; Li, Gengyin
Abstract: The deepening of the electricity-gas coupling provides a new dimension of system operational flexibility, but it also exacerbates the deliverability and availability issues on flexible ramping capabilities if the two systems are not operated coordinately. This paper presents a novel scheduling strategy to properly allocate ramp capabilities in integrated electricity-gas systems (IEGS) to tackle the uncertainty and variability of wind power. First, a polygon-based approach is introduced to identify the most severe ramping events taking wind power temporal correlation into account. To reduce the conservativeness, an adjustable polygon-based approach is further proposed to formulate the adjustable ramp capabilities constraints, which are subsequently integrated into the scheduling model. Then, a robust ramp capability-aware day-ahead IEGS scheduling model that comprehensively considers the uncertainties of wind power and gas load to ensure adequate ramp capabilities is developed, by which preventive plans for wind farms that serve as operational guidelines are derived by a geometric method while scheduling conventional units. The numerical results demonstrate the merits of the proposed method for dealing with ramping events and lowering the total cost in an uncertain environment. Compared to current approaches, the proposed method can slash the number of ramp shortages by about 50%. Highlights: Present a polygon-based method to identify ramp requirements efficiently. The adjustable polygon-based method provides superior economy and applicability. A new preventive plan for wind farm is developed through rigorous derivation. Case studies are conducted and the effect of key factors on solutions is discussed. The proposed scheduling strategy can slash the number of ramp shortage by about 50%.